(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
This article is devoted to the theoretical and experimental study of the strength and deformation characteristics of heavy concrete in a dry hot climate. Experimental research methods have been developed and the nature of the increase in strength and deformative properties of heavy concrete in a dry hot climate has been studied. Based on the conducted research, it was found that in a dry hot climate, the physical, mechanical and deformative properties of concrete change from the effect of temperature and humidity, which should be taken into account in the calculations. The creep deformation curves of concrete have a stepwise character and develop intensively mainly in the summer due to the effects of elevated temperature, low humidity and solar radiation of the environment.